2019
DOI: 10.37268/mjphm/vol.19/no.2/art.179
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Stress and Its Associated Factors Among Medical Students in Sabah, Malaysia Borneo

Abstract: Stress is accepted as the accumulation of unpleasant state of physical, mental and emotion on a person. Medical education has been known as one of the most stressful academic curriculum.  Hence, medical students may subjected to multiple psychological changes and challenges throughout the years of medical education.  The aim of this study was to determine the prevalence of stress and its associated factors among medical students. This cross sectional study was conducted from April to May 2018 in medical school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Social gatherings on campus were not allowed, and students were told to remain in their own dormitory or hostel until further notice. Studies conducted prior to COVID-19 had demonstrated a higher prevalence of stress in this same group of undergraduates [8]. This suggests an urgent need to establish factors associated with increased psychopathology in students.…”
Section: Introductionmentioning
confidence: 86%
“…Social gatherings on campus were not allowed, and students were told to remain in their own dormitory or hostel until further notice. Studies conducted prior to COVID-19 had demonstrated a higher prevalence of stress in this same group of undergraduates [8]. This suggests an urgent need to establish factors associated with increased psychopathology in students.…”
Section: Introductionmentioning
confidence: 86%
“…Perceived stress differs from actual stress in that it occurs when a person experiences emotions or feelings related to how much stress they feel over time. There has been a lot of study on perceived stress among medical and dentistry students [8], but less has been done on the psychosocial supports that can assist students deal with it [11]. Among students, optimism is a highly significant predictor of stress reduction.…”
Section: Perceived Stressmentioning
confidence: 99%
“…Although there is a huge of information on how stressful it is for medical and dentistry students, there are very few studies on undergraduates pursuing other courses [7][8][9][10]. Several studies have identified the role of psychological resources as a support system for managing stress [6].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several studies have been conducted to identify the stress level among university students. Overall, moderate to high-stress levels have been reported among university students from various majors (Ahad, 2019;Almojali et al, 2017;Amir Hamzah et al, 2019;Bisai & Chaudhary, 2017;Gedam et al, 2020;González Salinas et al, 2020;Musiun et al, 2019;Negi et al, 2019;Reddy et al, 2018;Reta et al, 2020;Zhai et al, 2020). Apart from that, some previous studies have tried identifying the predictors of stress and its association.…”
Section: Stressmentioning
confidence: 99%